2021
DOI: 10.2478/jccm-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke in Patients with Cancer: A Retrospective Cross-Sectional Study

Abstract: Introduction An increasing trend of cancer associated stroke has been noticed in the past decade. Objectives To evaluate the risk factors and the incidence of neoplasia in stroke patients. Material and Method A retrospective, observational study was undertaken on 249 patients with stroke and active cancer (SAC) and 1563 patients with stroke without cancer (SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…AIS is the second most common complication that involves the central nervous system in cancer patients, the first being cerebral metastases. 17 Viewed another way, one-in-ten patients with AIS have a history of remote or active cancer, making it critical to establish the best management strategies for LVO in this vulnerable group of patients. 18 In an autopsy study, it was reported that almost 15% of cancer patients had a stroke on post-mortem examination, with hemorrhagic and ischemic strokes being equally prevalent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AIS is the second most common complication that involves the central nervous system in cancer patients, the first being cerebral metastases. 17 Viewed another way, one-in-ten patients with AIS have a history of remote or active cancer, making it critical to establish the best management strategies for LVO in this vulnerable group of patients. 18 In an autopsy study, it was reported that almost 15% of cancer patients had a stroke on post-mortem examination, with hemorrhagic and ischemic strokes being equally prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a recent retrospective cross-sectional study, the most common stroke mechanism in cancer patients was cryptogenic (embolic stroke of unknown source), followed by large vessel disease. 17,21 Conventional stroke risk factors such as hypertension, diabetes, and atrial fibrillation are underrepresented in cancer-related stroke, invoking hypercoagulability and other cancer-specific causes of stroke. 10,22,23 Stroke patients with cancer are often excluded from receiving thrombolytic therapy due to concerns about brain metastasis, thrombocytopenia, coagulopathy, recent surgery, or overall poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 Studies investigating TOAST (Trial of Org 10172 in Acute Stroke Treatment) subtypes among patients with ischemic stroke and concomitant cancer reported cryogenic stroke to be the most frequent subtype. 14 , 17 , 18 Furthermore, Cestari et al 19 reported embolic ischemic stroke to be more common than non-embolic in ischemic stroke patients with underlying cancer, comprising 54% compared with 46%.…”
Section: Association Between Cancer and Different Subtypes Of Strokementioning
confidence: 99%